Prevalence, trauma history, and risk for posttraumatic stress disorder among nulliparous women in maternity care - Seng, Julia S. (2009)
OBJECTIVE: To estimate point prevalence and assess the association of types of trauma with posttraumatic stress disorder (PTSD) in a sociodemographically and racially mixed sample of women from both predominantly Medicaid and privately insured settings expecting their first infant. METHODS: Structured telephone diagnostic interview data were analyzed for prevalence of trauma exposure, PTSD, comorbidity, risk behaviors, and treatment-seeking among 1,581 diverse English-speaking nulliparous women. RESULTS: The overall rate of lifetime PTSD was 20.2%, 17% in the predominantly private-payer settings, 23% in the predominantly public-payer settings. The overall rate of current PTSD was 7.9%, 2.9% and 13.9% respectively. Those with current PTSD were more likely to be African American, pregnant as a teen, living in poverty, with high school education or less, and living in higher crime areas. Adjusted odds of having current PTSD were highest among those whose worst trauma exposure was abuse (OR = 11.9, 95% CI 3.6, 39.9), followed by reproductive trauma (OR = 6.1, 95% CI 1.5, 24.4). Health risk behaviors and exposures were concentrated among those with PTSD. CONCLUSION: These findings affirm that PTSD affects pregnant women. Women with PTSD in pregnancy were more like to have had exposures to childhood abuse and prior traumatic reproductive event, to have cumulative sociodemographic risk factors, comorbid depression and anxiety, and to have sought mental health treatment in the past. Obstetric risk behaviors occur more in women with PTSD. Research is needed to assess the effect of PTSD, a potentially modifiable source of perinatal morbidity, on obstetric outcomes.